ANALISIS YURIDIS TENTANG PELAKSANAAN PEMBATALAN HIBAH TANAH OLEH PEMBERI HIBAH - Hengky Prasetyo (Jurnal Ius Constituendum, 2016)
Grant is an agreement that is in everyday life, especially in modern society, the covenant is a constantly found in everyday life. Classified in the grant agreement freely in word freely demonstrated their prestige from one side only, while the other woods do not have to provide counter prestisnya. In principle a grant can not be withdrawn, but for the reasons specified by law and given certain circumstances, a grant it is possible to be withdrawn by the giver. The problems in this study are whether that is a consideration in the decision on the implementation of the cancellation judge grants of land by the grantor? And how the considerations of the judges are ideal to be applied in the cancellation of the grant of land by the grantor in Decision No. 95/Pdt.G/2004/PN Smg? The purpose of this research is to determine and analyze the consideration of judges in the implementation of the decision of cancellation of grants of land by the grantor; and to identify and analyze the consideration ofjudges ideal to be applied in the cancellation of the grant of land by the grantor No. 95/Pdt.G/2004/PN Smg. The method used in this research is normative juridical research.  Judge consideration by the Civil Code, Compilation of Islamic Law, Customary Law and Agrarian Law. The judge gives a decision that the grant made under the hand not have the force of law or legal defects that do not have binding legal force. The grant deed null and void, meaning not only canceled aktanya alone but the legal act also canceled. In an effort to cancellation of the grant by the grantor ideally Judge must look at aspects of the norms written and unwritten. Consequently sought the response of legal certainty for the parties involved to donate land. The judges must pay attention to how the decision to have the values of local wisdom into consideration in the cancellation of the land grant that will be actualized for the parties involved in making the grant deed.